Investigation of the Relationship Between Power Consumption and Noise Level During Hard Turning of CBN Tools and DIN 1.2367 Steel - AKKAŞ, Mehmet; YAVUZ, Mehtap; ŞAHİNOĞLU, Abidin (Gazi Universitesi Fen Bilimleri Dergisi Part C: Tasarim ve Teknoloji, 2021)
In this study, hard turning tests were carried out under dry cutting conditions on hardened DIN 1.2367 (55 HRC) steel material. The effect of the cutting parameter (three different cutting speeds, three feed rates and three cutting depths) on the power consumption and sound level values was investigated. A mathematical model has been created to estimate the power consumption and sound intensity. In this study, characterization study has also been carried out for DIN 1.2367 steel material and detailed information about the mechanical properties of the material has been obtained. According to the experimental results, as the feed rate, depth of cut and cutting speed increase; sound level and instantaneous current value are increasing. The increase in the cutting parameters increases the instantaneous current value, but the total processing time is reduced, thus reducing the total power consumption.
Keywords: Science (General); cbn; Science; Q; power consumption; Engineering (General). Civil engineering (General); Q1-390; sound level; hard turning; TA1-2040; din 1.2367; 7. Clean energy